2012
DOI: 10.1523/jneurosci.5288-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Adenylyl Cyclase Activity Is Necessary for Retinal Ganglion Cell Survival and Axon Growth

Abstract: Cyclic adenosine monophosphate (cAMP) is a critical second messenger mediating activity-dependent neuronal survival and neurite growth. We investigated the expression and function of the soluble adenylyl cyclase (sAC, ADCY10) in central nervous system (CNS) retinal ganglion cells (RGCs). We found sAC protein expressed in multiple RGC compartments including the nucleus, cytoplasm and axons. sAC activation increased cAMP above the level seen with transmembrane adenylate cyclase (tmAC) activation. Electrical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 63 publications
2
103
0
Order By: Relevance
“…Subsequent studies show that, depending on the duration of signaling, Epac converts cAMP from a proliferative into a differentiation signal (Kiermayer et al, 2005). In retinal ganglion cells, Epac links, both in vitro and in vivo, ganglion cell survival and axon growth to PKA and soluble AC (Corredor et al, 2012). As Epac regulates the phosphorylation of PKB/Akt in primary cortical neurons (Nijholt et al, 2008), this Epac signaling route probably supports neuronal survival.…”
Section: B Epac and The Brain 1 Role Of Epac In Neuronal Differentimentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies show that, depending on the duration of signaling, Epac converts cAMP from a proliferative into a differentiation signal (Kiermayer et al, 2005). In retinal ganglion cells, Epac links, both in vitro and in vivo, ganglion cell survival and axon growth to PKA and soluble AC (Corredor et al, 2012). As Epac regulates the phosphorylation of PKB/Akt in primary cortical neurons (Nijholt et al, 2008), this Epac signaling route probably supports neuronal survival.…”
Section: B Epac and The Brain 1 Role Of Epac In Neuronal Differentimentioning
confidence: 99%
“…In murine primary cortical neurons and HT-4 cells, Epac2 enhances PKB/Akt phosphorylation through Rap1 complexed to AKAP79/ 150 (Nijholt et al, 2008). In addition, Epac promotes neuronal survival and neurite growth through a nuclear complex composed of PKA and sAC (Corredor et al, 2012), suggesting that distinct cAMP microdomains maintained by sAC profoundly alter the signaling properties of Epac. The ability of Epac2 to promote remodeling of spiny synapses requires a distinct complex composed of neuroligin-3/PSD95/Rap complex (Woolfrey et al, 2009).…”
Section: B Epac and The Brain 1 Role Of Epac In Neuronal Differentimentioning
confidence: 99%
See 1 more Smart Citation
“…These functions include epithelial ion and fluid transport, sperm flagellar movement, gene expression, development and cell differentiation, ciliary beating in airways and oxidative phosphorylation in mitochondria (reviewed in Tresguerres et al, 2010a;Tresguerres et al, 2011). At the time of writing, sAC has additionally been shown to regulate the metabolic coupling between neurons and astrocytes (Choi et al, 2012), intraocular pressure (Lee et al, 2011), survival of retinal ganglion cells and axon growth (Corredor et al, 2012), aromatase gene expression and estradiol production (Chen et al, 2012a), pathologic activation of proteases in pancreatic acinar cells…”
Section: Physiological Roles Of Mammalian Sacmentioning
confidence: 99%
“…Therefore, we sought to identify a structurally unrelated sAC-selective inhibitor that can be used to complement KH7 and ddAdo. The catechol estrogens 2-CE and 4-CE inhibit pure sAC protein with low micromolar EC 50 s (Steegborn et al, 2005), and although they were shown to inhibit specific tmAC isoforms in vitro, they have been used as sAC-selective inhibitors in a number of physiologic systems (Pastor-Soler et al, 2003;Wu et al, 2006;Choi et al, 2012;Corredor et al, 2012;Di Benedetto et al, 2013). We used our two cell lines, sAC-overexpressing 4-4 cells and sAC KO MEFs, to definitively explore their utility in cell-based assays.…”
Section: Selectivity Of Ac Inhibitorsmentioning
confidence: 99%